2022
DOI: 10.26668/businessreview/2022.v7i5.e585
|View full text |Cite
|
Sign up to set email alerts
|

A study on the contribution that a business plan makes to the expansion of a small company

Abstract: Purpose: The purpose of this study is to investigate the contribution of business plan in the expansion of small company. No matter how big or small a business is or what stage it is in,it needs a business plan to improve how it runs internally and to describe and market the business to possible outside investors.   Theoretical framework: A business plan gives the company direction and brings employees together to work towards the same goals. When everyone works together, it's easier to manage time and resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Mahlangu (2019) reported that passion and the need to be independent were important among food truck entrepreneurs in Gauteng. Baa (2022) and Majid et al (2022) highlight the importance of implementing a business plan that will provide a competitive advantage over a long period of time to ensure sustainability. In this context, a sustainable business refers to a longstanding or continuous operation.…”
Section: Theoretical Perspective To the Studymentioning
confidence: 99%
“…Mahlangu (2019) reported that passion and the need to be independent were important among food truck entrepreneurs in Gauteng. Baa (2022) and Majid et al (2022) highlight the importance of implementing a business plan that will provide a competitive advantage over a long period of time to ensure sustainability. In this context, a sustainable business refers to a longstanding or continuous operation.…”
Section: Theoretical Perspective To the Studymentioning
confidence: 99%
“…The global business environment is increasingly competitive; as a result, firms need to be proactive and able to resist the competition in order to be successful. (Baa. 2022).…”
Section: Organizational Learningmentioning
confidence: 99%
“…There are possibilities that ultimately establishments may acknowledge the development of positions that do not right now exist, the analysis of which is outside the extent of conventional job analysis. Baa (2019) states that in an increasingly competitive global business climate, organizations must be proactive and resilient to succeed. This article highlights the strategies adopted by organizations to configure and analyze large amounts of job analysis data which facilitates human resource decision making.…”
Section: Introductionmentioning
confidence: 99%